Academic teaching in the era of COVID-19. Selected problems of academic teachers’ work in Poland against the background of the world situation - Łuszczek, Krzysztof; Chen, Chen; Lib, Waldemar (Adult Education Discourses, 2022)
The COVID-19 pandemic has significantly affected education in the vast majority of countries around the world. Educational systems were not prepared for this. This also extends to higher education. Certain measures have been taken in attempt to enable teaching in the new reality. The pandemic is global in nature and the changes in education have a similar aspect as well. After 12 March 2020, distance education was also introduced in Poland. Several months of distance learning have yielded some interesting experiences and shown the problems that arise when designing such educational systems. Due to the epidemic situation that is still far from being under control, it should be assumed that distance education will remain with us for longer. The article presents the results of research on distance learning in Poland in the first period of the pandemic in relation to the global situation. It focuses on academic teachers and the challenges they have faced when switching to distance learning.